Assisting Mathematics Teachers in Designing Differentiated Instruction Based on Contextual Learning - Maryati, Iyam; Azkiah, Firza; Apriyanti, Hilma Siti Nur; Yani, Indri (Fakultas Kewirausahaan Universitas Garut, 2024)
This community service program aims to assist mathematics teachers in designing differentiated instruction based on contextual learning. The background of this activity is the need to enhance teachers’ capacity in developing learning strategies that accommodate differences in students’ abilities, interests, and learning styles, so that the learning process becomes more inclusive and meaningful. The method used is descriptive, consisting of training, discussions, and mentoring in lesson design practices. This program emphasizes the application of differentiation principles in the context of mathematics learning that is relevant to everyday life. The results show that teachers gained a better understanding of differentiated instruction and were able to integrate contextual approaches into their lesson designs. Thus, this program is expected to strengthen teachers’ competencies in creating adaptive and relevant learning experiences that support 21st-century skills development.